2010
DOI: 10.1007/s11274-010-0351-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficient constitutive expression of thermostable 4-α-glucanotransferase in Bacillus subtilis using dual promoters

Abstract: 4-a-Glucanotransferases possess strong transglycosylation activity which has been used in various carbohydrate chemistry fields. Due to safety issues of the recombinant enzymes we chose Bacillus subtilis as an expression host to produce a thermostable 4-a-glucanotransferase from Thermus scotoductus (TSaGT). The HpaII promoter in the Gram-positive bacterial vector pUB110 was used first to express TSaGT gene in B. subtilis. However, the activity of TSaGT in B. subtilis was only 4% of that in our previous Escheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…A previous report demonstrated the expression level of AP in B. subtilis WB600 under the control of P HpaII . However, the expression and secretion levels were incomparable to those of other proteins [ 22 , 30 , 31 ]. Plasmid pBSG06 was introduced into B. subtilis 168, generating recombinant strain BSG107.…”
Section: Resultsmentioning
confidence: 99%
“…A previous report demonstrated the expression level of AP in B. subtilis WB600 under the control of P HpaII . However, the expression and secretion levels were incomparable to those of other proteins [ 22 , 30 , 31 ]. Plasmid pBSG06 was introduced into B. subtilis 168, generating recombinant strain BSG107.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous efforts have been carried out for enhanced hosts from the single factor to the network level (Anne, Economou, & Bernaerts, 2017; Song et al, 2015; van Dijl & Hecker, 2013; Westers et al, 2004), such as knockout of protease genes (Westers, Dijkstra, Westers, Van Dijl, & Quax, 2006; Wu, Lee, Tran, & Wong, 1991), fine‐tuning of gene expression at the levels of both transcription and translation (H.‐K. Kang et al, 2010; Phan, Nguyen, & Schumann, 2012), minimization of the dispensable genomic regions (Morimoto et al, 2008; Tanaka et al, 2013), and so on. In perspective of the industrial production, the optimized secretory pathway and engineered B. subtilis hosts would be combined to lead to next‐generation super‐secreting Bacillus cell factories.…”
Section: Discussionmentioning
confidence: 99%
“…Widner [33] found that gene expression was distinctly increased under the control of two or three tandem promoters in contrast to one alone in B. subtilis . Kang [34] also reported that two expression systems constructed by sequential alignment of a constitutive promoter for either α-amylase from B. subtilis NA64 or maltogenic amylase from B. licheniformis downstream of the Hpa II promoter elevated the TSaGT productivity by 11- and 12-fold, respectively, in comparison with the single Hpa II promoter system. Li [35] tried to construct multiple core-tac-promoters (MCPtacs) in tandem and found that integration of the phaCAB genes with the 5 copies of core-tac-promoters resulted in an engineered E. coli that can accumulate 23.7% polyhydroxybutyrate of the cell dry weight in batch cultivation.…”
Section: Discussionmentioning
confidence: 99%